PENGURANGAN KETIDAKPASTIAN PADA INTERAKSI AWAL PENGGUNA APLIKASI KENCAN ONLINE: Studi Fenomenologi Pada Pengguna Aplikasi Kencan Tinder - Safirah Hairulnisah (2021)
In the advanced technology era, people now can find a potential partner by utilizing a dating site or app, for example Tinder. Tinder user is basically strangers who have such high uncertainties in the initial encounter due to the lack of information about one another. Moreover, there is the absence of social presence in computer-mediated communication and the lack of non-verbal cues. Therefore, Tinder user tends to reduce uncertainties they experience by communicating while interactively seeking information about their partner. There are three interactive strategies which can be done in order to reduce uncertainty and gather information: question asking, self-disclosure, and relaxing target. This study uses qualitative method with phenomenological approach to explain the interactive information seeking strategy that was done by Tinder user in the initial interaction according to their own experience. All the research data are obtained by doing an interview with five informants and also from audio visual documentations which is found on YouTube. The data are analysed based on Uncertainty Reduction Theory and Social Penetration Theory. The result shown that in the initiation relationship, Tinder user inclines to throw general and not-so-confidential question to their partner. Tinder user also avoid to ask some questions to respect partner. The information they disclose is just about unintimate information. They tend to show their friendly side and humour to make their partner feel comfortable around them.